Mechanical properties of bamboo reinforced epoxy sandwich structure composites - Roslan, SAH; Hassan, MZ; Rasid, ZA; Zaki, SA; Daud, Y; Aziz, S; Sarip, S; Ismail, Z (Univ Malaysia Pahang, 2024)
Indexed by Scopus/WOS